Performance of Surfactant Flooding in Heterogeneous Two-Layered Porous Media - Fathaddin, M.T. (Trans Tech Publications Inc, 2010)
In this paper, simulation study was conducted to investigate the effect of spatial heterogeneity of multiple porosity fields on oil recovery, residual oil and microemulsion saturation. The generated porosity fields were fed into UTCHEM for simulating surfactant flooding in heterogeneous two-layered porous media. From the analysis, surfactant flooding was more sensitive than water flooding to the spatial distribution of multiple porosity fields. Residual oil saturation in upper and lower layers after water flooding was about the same with the reservoir heterogeneity. On the other hand, both residual oil and microemulsion saturation in the two layers after surfactant flooding became more equal as porosity distribution standard increased. Spatial heterogeneity of multiple porosity fields had only a small effect on residual oil saturation and recovery factor. The variation of recovery factor due to the reservoir heterogeneity was under 4.2%.